2003
DOI: 10.1046/j.1439-0264.2003.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Macro and Microstructural Organization of the Dog's Caudal Mesenteric Ganglion Complex (Canis Familiaris‐Linnaeus, 1758)

Abstract: The caudal mesenteric ganglion (CMG) is located ventral to the abdominal aorta involving the initial portion of the caudal mesenteric artery. Its macro and microstructural organization was studied in 40 domestic dogs. From the CMG, there were three nerves: the main hypogastric, the left hypogastric and the right hypogastric. The main hypogastric nerve emits two branches: the left colonic nerve and the cranial rectal nerve. Afterwards they give rise to branches to the descending colon (colonic nerves) and rectu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
7
8
0
Order By: Relevance
“…Inside each ganglionic unit the most prominent cellular elements were ganglion neurons, glial cells and SIF cells, which were altogether named as the ganglion morphological triad, similar to that reported for the dog's celiac and caudal mesenteric ganglia by Ribeiro et al [2002] and Gagliardo et al [2003], respectively. Given this morphological arrangement, the SCG from dogs, cats and horses is much better characterised as a ganglion complex, and this structural arrangement might be due to the presence of very specific SCG innervation territories and target organs as seen by injecting retrograde neurotracers that revealed the exact localisation of the labelled neurons in SCG [Bowers and Zigmond, 1979;Flett and Bell, 1991;Luebke and Wright, 1992;Andrews et al, 1996;Hayakawa et al, 2000].…”
Section: Microstructuresupporting
confidence: 74%
See 1 more Smart Citation
“…Inside each ganglionic unit the most prominent cellular elements were ganglion neurons, glial cells and SIF cells, which were altogether named as the ganglion morphological triad, similar to that reported for the dog's celiac and caudal mesenteric ganglia by Ribeiro et al [2002] and Gagliardo et al [2003], respectively. Given this morphological arrangement, the SCG from dogs, cats and horses is much better characterised as a ganglion complex, and this structural arrangement might be due to the presence of very specific SCG innervation territories and target organs as seen by injecting retrograde neurotracers that revealed the exact localisation of the labelled neurons in SCG [Bowers and Zigmond, 1979;Flett and Bell, 1991;Luebke and Wright, 1992;Andrews et al, 1996;Hayakawa et al, 2000].…”
Section: Microstructuresupporting
confidence: 74%
“…Therefore, SCG was divided into distinct compartments by capsular septa of connective tissue as reported for mammalian sympathetic ganglia by Gabella et al [1988], Szurszewski and King [1989], Szurszewski and Miller [1994], Miolan and Niel [1996], Schmidt [1996], Ribeiro et al [2002], Gagliardo et al [2003] and Ribeiro et al [2004]. Gabella et al [1988] described that the sheep's SCG is composed of several ganglion units, each one being constituted of neurons and glial capsule.…”
Section: Microstructurementioning
confidence: 99%
“…In these studies we always found the CaMG as the paired structure. Gagliardo et al (2003) have proved the canine CaMG to be the impaired structure. This well documented study performed on 40 individuals are in disagreement with a report (Zacharko et al 2004) describing the localisation of neurones supplying the prostate gland and claiming that the retrogradely traced neurones were found within bilateral CaMG-s.…”
Section: Discussionmentioning
confidence: 95%
“…Textbooks of veterinary anatomy contain only general descriptions of the abdominal part of the sympathetic nervous system, especially its caudal portion (Klimov and Akajewski 1953, Nickel et al 2004, Koenig and Liebich 2007. Except some contributions (Gagliardo et al 2003, Berghes 2007, the literature lacks of wider information on the caudal mesenteric ganglion gross anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation